Exploring Elementary Students’ Invention Ingenuity in Science Labs - Mustafa Jwaifell; Osama M. Kraishan (Elementary Education Online, 2023)
Invention is one of the strongest forces that lead to human civilization. Without a clear picture and scientific understanding of invention, it can hardly be any continuity of the past, present, or future This study carried out in Ma’an, a poor-environment area of Southern Governorate in Jordan, with 50 ninthgrade students: 25 males and 25 females aged 15 years old, has one aim which is to explore ninth-grade students’ invention ingenuity in science labs. Fifty ninth-grade students from two schools of Ma’an directorates of education were chosen randomly to participate in inventing Products to solve five problems asked them in science labs. A mix of qualitative and quantitative methodology was used to answer the study questions. Results of the study showed the students invented good products for the solving problems, teachers appreciated the Invention in Science Labs framework as an instructional model, and students valued this kind of learning experience. Recommendations were included in this study.